PENGARUH KOMPOS SLUDGE PKS TERHADAP PRODUKSI PADI SAWAH (Oryza sativaL) YANG DITANAM DENGAN SRI MODIFIKASI - M. Ridho Endeni; Arman Effendi; Erlida Ariani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2022)
The research was conducted at BBI Pekanbaru. Address, Jl. KaharudinNasution, MarpoyanDamai, Pekanbaru City, Riau. This research was conducted from May to August 2021. This study consisted of five doses of sludge fertilizer using three replications and using a randomized block design. The treatments given were various doses of mud consisting of 3 doses, namely: S0= 0 t.ha-1 (0 kg per plot), S1= 10 t.ha-1 (3 kg per plot), S2= 20 t .ha-1 (6 kg per plot). Parameters observed number of productive tillers, the number of grainy grain, dry grain weight per plot, weight of 1.000 grains of pithy grain. The data obtained were analyzed statistically using Analysis of Variance (ANOVA) then further tested with Duncan's multiple distance test at a level of 5% using the Satker application system (SAS). The results showed that the application of PKS sludge compost fertilizer had an effect on the maximum number of tillers, number of productive tillers, number of pithy grain per panicle, and the weight of dry milled grain per plot with the best PKS sludge compost fertilizer at a dose of 20 ton.ha-1. Based on the research results obtained, To obtain the best lowland rice cultivation, it is recommended to use compost from palm oil waste (sludge) with the SRI method at a dose of 20 ton.ha-1.Keyworsd: sludge, doses, rice plant